Effect of heat acclimation on metabolic adaptations induced by endurance training in soleus rat muscle. Issue 16 (17th August 2021) - Tardo‐Dino, Pierre‐Emmanuel; Taverny, Cindy; Siracusa, Julien; Bourdon, Stéphanie; Baugé, Stéphane; Koulmann, Nathalie; Malgoyre, Alexandra
Abstract: Aerobic training leads to well‐known systemic metabolic and muscular alterations. Heat acclimation may also increase mitochondrial muscle mass. We studied the effects of heat acclimation combined with endurance training on metabolic adaptations of skeletal muscle. Thirty‐two rats were divided into four groups: control (C), trained (T), heat‐acclimated (H), and trained with heat acclimation (H+T) for 6 weeks. Soleus muscle metabolism was studied, notably by the in situ measurement of mitochondrial respiration with pyruvate (Pyr) or palmitoyl‐coenzyme A (PCoA), under phosphorylating conditions ( V ˙ max ) or not ( V ˙ 0 ). Aerobic performance increased, and retroperitoneal fat mass decreased with training, independently of heat exposure ( p  < 0.001 and p  < 0.001, respectively). Citrate synthase and hydroxyl‐acyl‐dehydrogenase activity increased with endurance training ( p  < 0.001 and p  < 0.01, respectively), without any effect of heat acclimation. Training induced an increase of the V ˙ 0 and V ˙ max for PCoA ( p  < .001 and p  < .01, respectively), without interference with heat acclimation. The training‐induced increase of V ˙ 0 ( p  < 0.01) for pyruvate oxidation was limited when combined with heat acclimation (−23%, p  < 0.01). Training and heat acclimation independently increased the V ˙ max for pyruvate (+60% p  < 0.001 and +50% p  = 0.01, respectively), without an additive effect of the combination. Heat acclimation doubled the training effect on muscle glycogen storage ( p  < 0.001). Heat acclimation did not improve mitochondrial adaptations induced by endurance training in the soleus muscle, possibly limiting the alteration of carbohydrate oxidation while not facilitating fatty‐acid utilization. Furthermore, the increase in glycogen storage observed after HA combined with endurance training, without the improvement of pyruvate oxidation, appears to be a hypoxic metabolic phenotype. Abstract : We studied the consequences of heat acclimation combined with endurance training on metabolic adaptations of skeletal muscle. Heat acclimation (HA) did not improve training‐induced adaptations of mitochondrial maximal oxidation capacities for carbohydrates (Vmax PYR) or fatty acids (Vmax PCOA) in the soleus. Despite this lack of facilitation for CHO oxidation, we observed a synergistic effect of heat and endurance training on glycogen storage which may be beneficial for the glycolytic pathway. This adresses the issue of this combined conditioning as an alternative in preparattion for sports requiring glycogen storage or glycoltyic flux.